2018
DOI: 10.1039/c8cc08289h
|View full text |Cite
|
Sign up to set email alerts
|

Tracking mitochondrial 1O2-ROS production through a differential mitochondria-nucleoli fluorescent probe

Abstract: A dual-emissive fluorescent probe enabled unique tracking of 1O2-ROS species through a differential mitochondrial–nucleoli localization dynamic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Recent work has yielded additional probes to measure different ROS species in the mitochondria. RC334 was shown to selectively monitor mitochondrial singlet oxygen, 1 O 2 , without interference from pH and membrane potential, as well as other ROS species such as H 2 O 2 and OH radicals . Similarly, PBD-B is a ratiometric fluorescence reporter that selectively responds to superoxide over other ROS species over a wide range of concentrations both in vitro and in vivo .…”
Section: Mitochondrial Rosmentioning
confidence: 99%
“…Recent work has yielded additional probes to measure different ROS species in the mitochondria. RC334 was shown to selectively monitor mitochondrial singlet oxygen, 1 O 2 , without interference from pH and membrane potential, as well as other ROS species such as H 2 O 2 and OH radicals . Similarly, PBD-B is a ratiometric fluorescence reporter that selectively responds to superoxide over other ROS species over a wide range of concentrations both in vitro and in vivo .…”
Section: Mitochondrial Rosmentioning
confidence: 99%
“…Even little changes of mitochondrial membrane potential could result a huge influence on the cell viability and are closely connected with a series of diseases. Therefore, development of sensitive methods to monitor mitochondrial membrane potential is particularly important 5–10…”
Section: Introductionmentioning
confidence: 99%
“…Flores-Cruz et al 107 reported a fluorescent probe ( 25 ) to track the 1 O 2 generated in mitochondria through a unique mitochondria-to-nucleoli shuttle (Fig. 14C).…”
Section: Flavylium Based Fluorescent Probesmentioning
confidence: 99%